Moderasi Beragama di Indonesia (Perspektif Adaptasi Antar-Budaya dalam Islam dan Katolik) - Hironimus Bandur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2021)
Religious moderation has become a trending issue in Indonesia in thelast five years. This paper attempts to answer two important questions:first, what is the basic teologic for doing religious moderation Muslimsand Catholics in Indonesia; and second, how Young Yun Kim’s theoryof cross-cultural adaptation inspires Muslims and Catholics inimplementing religious moderation in Indonesia. With literature studiesfound; first, the Quran and the Bible are authentic sources in efforts tomoderate religion in Indonesia. Second, Muslims and Catholics are tworeligions that are close to culture, therefore the theory of cross-culturaladaptation becomes an inherent part of the existence of Muslims andCatholics in facing the local tradition. The Catholic Church traditionuses the term inculturation, while the Muslim tradition calls it,culturalization. However, religious moderation is not synonymous withinculturation and culturalization. Inculturation and culturalizationare models of cross-cultural adaptation to the paradigm of religiousmoderation. Here religion and local traditions are interconnected butalso intercorroborated.